From endurance to power athletes: The changing shape of successful male professional tennis players - Gale-Watts, A. S.; Nevill, A. M. (European Journal of Sport Science, 2016)
The aim of the present study was to identify whether the relative shape and size characteristics of elite male tennis players have changed over time, and in addition whether any anthropometric parameters characterise the more successful players in Grand Slam tournaments. The height and body mass of the players qualifying for the first round in all four Grand Slam tennis tournaments during the period 1982-2011 was obtained, and successful players defined arbitrarily as those reaching round 3 or beyond. Body mass index (BMI) and the reciprocal ponderal index (RPI) were used as our measures of body shape. Multilevel modelling was used to explore the trend over time using non-linear polynomials. The results suggest that the body shape of elite tennis players has changed over time, with a non-linear (cubic polynomial regression model) increase in BMI and a similar non-linear decline in the RPI. BMI, reflecting greater muscle mass rather than greater adiposity, has emerged as an important factor associated with success, identified by a significantly positive (steeper) "successful player"-by-"year" interaction term. The evidence that the RPI of elite tennis players has also decreased over time, together with a significantly negative "successful player"-by-"year" interaction term, suggests that a more linear (ectomorphic) body shape is a less important factor in terms of success. These results suggest that elite male tennis players are becoming more power trained athletes as opposed to endurance athletes, with greater muscle mass being an important factor associated with success in all Grand Slam tournaments.